2000
DOI: 10.1210/jcem.85.9.6842
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Microsatellite Polymorphism Influences the Development of Insulin Dependency in Adult-Onset Diabetes Patients with the DRB1∗1502-DQB1∗0601 Allele and Anti-Glutamic Acid Decarboxylase Antibodies

Abstract: Recently, several studies have demonstrated that tumor necrosis factor microsatellite polymorphism (TNFalpha) contributes to the susceptibility of type 1 diabetes. This study investigates the influence of TNFalpha on the predisposition to insulin dependency in adult-onset diabetic patients with type 1 diabetes-protective human leukocyte antigen haplotypes. The TNFalpha of three groups of DRB1*1502DQB1*0601-positive diabetic patients who had initially been nonketotic and noninsulin dependent for more than 1 yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2005
2005
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Moreover, TNFa12 has been demonstrated to be associated to LADA in the Japanese population [33]. In contrary to our findings, none of the TNFa alleles manifested an association to type 1 diabetes in an Italian population [11].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, TNFa12 has been demonstrated to be associated to LADA in the Japanese population [33]. In contrary to our findings, none of the TNFa alleles manifested an association to type 1 diabetes in an Italian population [11].…”
Section: Discussioncontrasting
confidence: 99%
“…Although the DQB1 region was examined in some of the studies on the relationship with autoimmune markers (4,15,32) and in some family studies (21,26), direct comparison was not possible, despite the fact that a few studies have examined DQB1*0201 (8,20,26,32) or DQB1*0601 (15,20,22). This is so because these studies reported on genotype combinations (see below) and not on the frequency of the specific genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest was the increased prevalence of the DRB1*150101-DQB1*060101 haplotype among Bahraini patients with type 2 diabetes. Previous studies which looked into the possible role of DQB1*0601 reported that in GAD-positive, DRB1*1502-QB1*0601-positive patients initially diagnosed as having type 2 diabetes, tumor necrosis factor alpha was associated with predisposition to subsequent insulin dependency (19,22). In the Finnish study (8), the frequency of the "type I protective alleles" HLA-DQB1*0602 and *0603 was similar in control subjects and GAD-positive and GADnegative type 2 diabetes patients, but lower in type 1 diabetes subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the age of onset of type 1 diabetes is variable and it has been reported that the frequencies of some type 1 diabetes susceptibility HLA class II alleles and/or haplotypes may vary depending on the age of disease onset [1,2]. It has also been reported that several polymorphisms of MHC classes I and III genes and interleukin genes are associated with the age at onset of type 1 diabetes [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%